Collaboration, Innovation and Time: A shared-journey through child psychiatric consultation in the school setting - Coffey, Sara (Psychiatr Serv, 2019)
INTRODUCTION: Similar to reports across the United States, roughly 20% of students in our community are diagnosed with emotional and behavioral disturbances. These problems often manifest in our school settings and although several universal, targeted and individual mental health services are in place, students and teachers still struggle in the classroom. OBJECTIVE: With this need in mind our team set out to provide collaborative, innovative support to our public school system, while offering a novel training opportunity for child and adolescent psychiatry fellows. METHOD: Working collaboratively, our child psychiatry team offered direct clinical care and consultation in the school-based clinic. As our relationship progressed the psychiatry team offered ongoing professional development and consultation to teachers, followed by district-wide implementation. DISCUSSION: Engaging and working in school settings is not without challenges. Essential to any effective partnership is communication, respect and trust. Our multi-year partnership, incorporating fellowship training offered a mutually beneficial experience for educators and psychiatry trainees alike.